2011
DOI: 10.1371/journal.pone.0020270
|View full text |Cite
|
Sign up to set email alerts
|

Var2CSA Minimal CSA Binding Region Is Located within the N-Terminal Region

Abstract: Var2CSA, a key molecule linked with pregnancy-associated malaria (PAM), causes sequestration of Plasmodium falciparum infected erythrocytes (PEs) in the placenta by adhesion to chondroitin sulfate A (CSA). Var2CSA possesses a 300 kDa extracellular region composed of six Duffy-binding like (DBL) domains and a cysteine-rich interdomain region (CIDRpam) module. Although initial studies implicated several individual var2CSA DBL domains as important for adhesion of PEs to CSA, new studies revealed that these indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
75
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 45 publications
0
75
1
Order By: Relevance
“…Core CSA-binding Site Lies within DBL2X Domain-It has been suggested that the minimal CSA-binding region in VAR2CSA lies within DBL2X-ID2b, with the need of flanking domains for full affinity binding (19,20). Here we have analyzed shorter fragments of VAR2CSA to further map the regions required for CSA binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Core CSA-binding Site Lies within DBL2X Domain-It has been suggested that the minimal CSA-binding region in VAR2CSA lies within DBL2X-ID2b, with the need of flanking domains for full affinity binding (19,20). Here we have analyzed shorter fragments of VAR2CSA to further map the regions required for CSA binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has suggested that the minimal CSA binding region in VAR2CSA is DBL2X-ID2b, with the need for DBL1X or DBL3X for full affinity binding (19,20). In continuation of this work we made further truncations of VAR2CSA, focusing on the DBL2X region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VAR2CSA harbors 6 DBL domains, several of which have been implicated in CSA binding, although no consensus has been reached as to whether all or only individual DBL domains interact with CSA. 32,[39][40][41][42][43] To investigate the putative cooperative nature of the VAR2CSA/CSA interaction, we attempted to inhibit domain-specific regions of VAR2CSA using antibodies against the individual DBL domains. 26 We reasoned that these DBL domainspecific antibodies might interfere with substrate-induced allosteric changes and, thus, with the degree of cooperativity.…”
Section: Antibodies Against Dbl Domains Affect Cooperativitymentioning
confidence: 99%